(untitled) (Bisanzio e l’Occidente, 2019)
The paper deals with the patronage of Constantine and of his mother Helena in the New Rome and beyond. Through the exam of buildings, honorary colums and monuments, jewels, illuminated manuscripts and, particularly, sources, the artistic endeavours of the emperors are considered as to delineate a future, more in deep, research.